Genótipos das cepas de H. pylori vacA e Alelos cagA e sítios de fosforilação EPIYA em uma comunidade urbana de Fortaleza - Gonçalves, Maria Helane Rocha Batista (2010)
The H. pylori infect currently half of the world’s population and is related to the development of gastric disorders. The Enterotest is a minimally invasive method that can be used for detection of H. pylori through endoscopic not. The objective of this study was to evaluate the sensitivity and specificity of Enterotest opposite the Respiratory Testing and studying the genetic profile of strains of H. pylori individuals resident in the Community College Park. The gastric juice was collected from Enteroteste, and held the culture and the extraction of DNA from H. pylori. The genotyping of strains was carried out by the PCR technique and phosphorylation sites EPIYA sequencing participated in the study 50 individuals, positive and negative 7 43 for infection H. pylori through Respiratory Test. Culture and PCR from Enteroteste showed sensitivity of 86% and 77%, respectively, with 100% specificity in both methods. 33 strains were positive, genotipadas as Cow being 39.4% Cow s1m1; 15.2% Cow s1m2; 18.2% Cow s2m2 27.2% with Cow s profile with absence of allele m. Were positive 66.6% Bran of strains being profiled 54.5% EPIYA-ABC, 41.0% EPIYA-ABCC and 4.5% EPIYA-AB. The Enterotest proved to be a reliable method with great sensitivity and specificity for identification of H. pylori through cultivation and PCR technique. Most strains expressed alelo Cow s1, with a predominance of subtype s1b and allele combination s1m1. More than half of the studied strains expressed gene Shit and most of these strains were 3 or 4, phosphorylation sites profiled EPIYA-ABC or EPIYA-ABCC. The genetic profile presented by these strains is described for South America and nonstandard Asia, most strains circulating in the community have important potential pathogenic. The Enterotest is a safe method, sensitive and specific detection of H. pylori.